Formulas for failure?: Were the Doha tariff formulas too ambitious for success? - Laborde Debucquet, David; Martin, Will (Cambridge University Press, 2015)
This paper views tariff-cutting formulas as a potential solution to the free-rider problem that arises when market opening is negotiated bilaterally and extended on a most-favored-nation basis. The negotiators in the Doha Agenda chose formulas that are ideal from an economic efficiency viewpoint in that they most sharply reduce the highest – and most economically – costly tariffs. When the political support that gave rise to the original tariffs is considered, however, this approach appears to generate very high political costs per unit of gain in economic efficiency. The political costs associated with the formulas appear to have led to strong pressure for many, complex exceptions, which both lowered and increased uncertainty about members' market access gains. Where tariff cuts focus on applied rates, it seems likely that a proportional cut rule would reduce the political costs of securing agreements. However, detailed examination of the Doha proposals with their product exceptions suggests that negotiators are likely to find cuts with exceptions politically attractive but economically costly when cuts are based on bound tariffs with different degrees of binding overhang.